PENDIDIKAN KARAKTER BERBASIS PESANTREN: STUDI KASUS DI SMP PUNCAK DARUS SALAM PAMEKASAN - Fauzan - (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2015)
This article attempts to examine the implementation of pesantren-based character education with a locus of Junior High School Puncak Darus Salam located in Potoan, Palengaan, Pamekasan, Madura. In his analysis,the author uses a qualitative-phenomenological approach in which the data is based on the model of Miles and Huberman by interpreting the data interactively and continouesly. This research found that the cultivation of character education in SMP Puncak Darus Salam is the implementation of its vision and mission, which is to generate generation with the Qur’an and Sunnah-based special characters. The success of the character education implemented at the school is mainly supported by the integration of the school and pesantren curriculum. This article will elaborate further the character education focusing on three aspects: affective, cognitive, and psychomotor.Keywords: Pendidikan Karakter, Afektif, Kognitif, Psikomotorik